Bitcoin, Libra and Central Bank Digital Currencies — Elements of a New Monetary System? - Jonas Groß; Bernhard Herz; Jonathan Schiller (Wirtschaftsdienst)
Abstract After the launch of Bitcoin in 2008 and the subsequent introduction of more than 6,600 cryptocurrencies, a new wave of innovative payment projects is currently on its way, including innovations like Libra — designed as a supranational stable coin — and central bank digital currencies (CBDCs). Various interrelations link these private and public projects. Contrary to the original intentions, Bitcoin has not developed into a widespread means of payments, not the least due to its considerable price volatility. Its most significant contribution could be the „proof of concept“ for an innovative, private means of payment outside the conventional monetary system. In contrast, Libra is designed as a rather conventional means of payment with close relations with the existing banking sector, which raises numerous policy questions concerning monetary and financial stability. Central bank digital currencies could be viewed as a public sector response to these private projects to secure central banks’ predominant role in the monetary system of the future.